Volatility hedging model for precious metal futures returns - Roengchai Tansuchat (2018)
© Springer International Publishing AG 2016. This study attempts to evaluate appropriately the optimal hedge ratio and hedging effectiveness between spot and futures returns of precious metals with a special concern in gold, silver, and platinum. We employ the Markov switching dynamic copula model to measure the dependence structure between spot and futures returns of these precious metals and then evaluate the hedging strategies. Evidence from this study can bring about the contribution to the discussion on this area.